Standard specification for copper alloy bullet jacket cups
This specification establishes the requirements for bullet jacket preform cups produced of Copper Alloy UNS No. C22000 for processing into bullet jackets of the following types and class; Type I-Caliber 0.30., Type II-Caliber 0.45., Type III-Caliber 0.50., Type IV-As specified in the contract or order., Class I-Not annealed., and Class II-Annealed.